2015
DOI: 10.1166/jnn.2015.9771
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Titania Nanotubes in Bone Biology

Abstract: Orthopedic implants, including artificial joints and fracture fixation devices, have helped to restore the physical independence of many patients, thereby improving the quality of their lives. Titania (Ti) and its alloys are better implant materials than stainless steel and Co-Cr alloys owing to their superior mechanical properties and biocompatibility; however, Ti-based implants may sometimes fail, leading to repeated surgeries. With the recent advancements in nanotechnology, the nanosurface modifications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…It has been reported that surface characteristics including physical topography and chemical components are identified as important factors affecting the subsequent osseointegration 34,35) . Implant surface with TiO2 nanotube arrays exhibited enhanced osseointegration and improvement of stability 36) . In particular, several previous studies have revealed higher bone-implant contact and gene expression levels of OCN, COL and ALP in the bone attached to 70-nm-diameter TiO 2 nanotubes [36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that surface characteristics including physical topography and chemical components are identified as important factors affecting the subsequent osseointegration 34,35) . Implant surface with TiO2 nanotube arrays exhibited enhanced osseointegration and improvement of stability 36) . In particular, several previous studies have revealed higher bone-implant contact and gene expression levels of OCN, COL and ALP in the bone attached to 70-nm-diameter TiO 2 nanotubes [36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…Implant surface with TiO2 nanotube arrays exhibited enhanced osseointegration and improvement of stability 36) . In particular, several previous studies have revealed higher bone-implant contact and gene expression levels of OCN, COL and ALP in the bone attached to 70-nm-diameter TiO 2 nanotubes [36][37][38] . It is also reported that HA could potentially improve osseointegration 39,40) , and Ca 2+ and PO4 3− ions provided necessary substances for osteoblast maturity and mineralization 35) .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, titanium (Ti)-based metallic materials have been widely optimized for bone repair due to their mechanical properties and resistance to corrosion following the transplantation [66][67][68]. It has been shown that titanium scaffolds are effectively colonized by osteoblasts responsible for bone formation and this process may be enhanced via additional modifications of the scaffold surface by its roughening, coating with HA or graphene oxide (GO), as well as its biofunctionalization with bioactive molecules such as heparin and bone morphogenetic protein 2 (BMP-2) [69][70][71][72].…”
Section: Synthetic Biomaterialsmentioning
confidence: 99%
“…Among the different strategies for surface modification, anodic oxidation has attracted much attention. Anodic oxidation (AO) is an easy, economical way to fabricate controllable nano-scale surface topography 7) . We have previously reported that the TiO 2 surface created by anodic oxidation induced bone-like apatite layer precipitation in simulated body fluid soaking test and increased the gene expression of bone-specific marker osteoprotegrin compared to the control Ti surface 8) .…”
Section: Introductionmentioning
confidence: 99%